If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x)(x + -9) = 0 Remove parenthesis around (5x) 5x(x + -9) = 0 Reorder the terms: 5x(-9 + x) = 0 (-9 * 5x + x * 5x) = 0 (-45x + 5x2) = 0 Solving -45x + 5x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5x'. 5x(-9 + x) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-9 + x)' equal to zero and attempt to solve: Simplifying -9 + x = 0 Solving -9 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + x = 0 + 9 x = 0 + 9 Combine like terms: 0 + 9 = 9 x = 9 Simplifying x = 9Solution
x = {0, 9}
| 7.2=5x-5.3 | | -12*x=8 | | 10+8c=42 | | 3y-8+y+48=8y+40-6y | | 7x+8y-6x-5y= | | 3x-(x-8)=2(x+4) | | (x+3)(x-4)= | | 3A+10+2+c=A+A+20+c | | 2.5x+.25x=2.25+x | | 0.666x-6=9 | | 7-x=-11 | | 0.428x+5=8 | | (8x)(x+8)=0 | | 20=2(y+3)+5y | | 0.22y-0.8=0.12y+1-0.5y | | -34=7(u-7)-2u | | 5(5x+2)-4(x+3)=42 | | 5(t-2)+5t=5(2t+4)-9 | | 9=3w+7(w+7) | | 2(3x-5)=14 | | 2t-18=-54+8t | | 4w^3-3w^2-28w-21=gcf | | 5(3x+2)-4(x+3)=42 | | 9x-(2x+6)= | | 3u+4=-17 | | x^2+14x+70=0 | | 3(3x+2)-7(x+8)=126 | | -y+174=84 | | 2x-7=5x-40 | | 6+(10-5)2-20= | | 251=75-y | | 25=158-w |